RETRACTED: A Dynamic Analysis of the Asymmetric Effects of the Vocational Education and Training on Economic Growth, Evidence From China - Xia, Linzhong; Ali, Arshad; Wang, Haotian; Wu, Xun; Qian, Dake (Frontiers in Psychology, 2022)
Since 2010, China's economic growth has stagnated due to unbalanced regional industrial structure and lack of sufficient qualified technical personnel. This study used a nonlinear autoregressive distributed lag (NARDL) model to examine the asymmetric effects of secondary vocational education (SVET) and higher vocational education (HVET) and their interaction with high-tech industries on economic growth over the period 1980-2020. The findings show that an increase in secondary vocational education (SVET) significantly boosts long-term economic growth, while a decrease in secondary vocational education (SVET) insignificantly reduces long-term China economic growth. Likewise, the upward change in higher vocational education (HVET) promotes and the downward fluctuation in higher vocational education (HVET) significantly reduces China's long-term economic growth. The contribution of secondary vocational education and high-tech industry interaction (SVET*HTI) to China's economic growth is not significant. However, the interaction between higher vocational education and high-tech industries (HVET*HTI) has significantly boosted China's economic growth. Strategically, the study analysis suggests that economic transition prosperity can be achieved by encouraging higher vocational education and the equal development of high-tech industries in all regions. In addition, this study also proposes to cultivate high-quality talents related to high-tech development and modern industrial innovation and upgrading through higher vocational education, improve productivity, and promote the country's intensive development.